Host range testing and life history of the defoliator Hymenomima nr. memor: an unsuitable biological control agent for Schinus terebinthifolia in the U.S.A. Issue 11 (1st November 2016) - Broggi, E.; Dyer, K.; Wheeler, G. S.
ABSTRACT: Host range of larvae of Hymenomima nr. memor (Lepidoptera: Geometridae) was examined in quarantine to evaluate its suitability as a biological control of Brazilian peppertree, Schinus terebinthifolia . Brazilian peppertree, S. terebinthifolia is an environmental and agricultural weed from South America that had invaded many subtropical and tropical areas of the world including Florida and Hawaii, USA. Laboratory life history and quarantine host range studies of H . memor were conducted with no-choice feeding tests. These tests included eight species of the Anacardiaceae and one species of Sapindaceae. Larvae of H. memor had five to six instars with each head capsule width increasing by 1.68-X. Development time from neonate to adult was 46.7 ± 2.2 days. In host range tests, neonates completed development to the adult stage on all non-target species, except Toxicodendron radicans . Moreover, developmental times were delayed and pupal weights were reduced for larvae fed Spondias purpurea leaves. Due to the broad host range exhibited by H. memor larvae, this species will not be considered as a biological control agent of S. terebinthifolia in the continental U.S.A.